Meningkatkan Hasil Belajar Dengan Model Contextual Teaching and Learning pada mata pelajaran IPS di SD Inpres Waioti - Lukas Bera (Peneliti.net, 2020)
This study aims to improve students learning achievement by Contextual Teaching and Learning toward 3rd grade students in SD Inpres Waioti. This research is class action research, the subject of this research is the 3rd grade students of SD Inpres Waioti, which numbered 23 students.. The data collecting techniques using observation and the result of test for work. The data analysis techniques that used in this research is quantitative analysis. The result of this research shows the process of learning by using Contextual Teaching and Learning which can increase toward cycle number 1 with completeness 87% refers to the deficiency of cycle 1, then repaired the learning process, in cycle II the percentage of completeness become 100%. Then from the result of this research can be concluded that students’ learning outcomes got the changes towards the better after using Contextual Teaching and Learning in social study selling and buying material.